Atlantic Cod Show a Highly Variable Sensitivity to Electric‐Induced Spinal Injuries. Issue 1 (8th September 2016) - Soetaert, M.; De Haan, D.; Verschueren, B.; Decostere, A.; Puvanendran, V.; Saunders, J.; Polet, H.; Chiers, K.
Abstract: Pulse trawling is the most promising alternative to conventional beam trawls targeting Sole Solea solea (also known as Solea vulgaris ), but due to the electric fields created by electrotrawls spinal injuries are reported in gadoid round fishes such as Atlantic Cod Gadus morhua . This study aimed to investigate the variability in the occurrence of electric‐induced spinal injuries in cod. Four groups of cod, each originating from a different wild or farmed stock, were exposed to the pulses used by electrotrawls targeting Sole. Effects were analyzed based on behavior, mortality, and lesions up to 14 d after exposure, and morphological characteristics such as size, somatic weight, muscularity, the number of vertebral bodies, and the vertebral mineral contents of animals were compared among different cohorts. Second, the influence of factors such as water temperature, electrode diameter, and pulse type and amplitude were tested. Electrode diameter and pulse amplitude showed a positive correlation with the intensity of the fish's reaction. However, the present experiments confirmed that cod also show variable vulnerability, with injury rates ranging from 0% to 70% after (almost) identical exposures near the electrode. This indicates that these injuries are not only determined by the pulse parameter settings but also by subtle, fish‐specific factors. Although the absence of a sensitive group of cod did not enable the elucidation of the conclusive factor, the effect of physiological and morphological factors such as intervertebral ligaments and rearing conditions during early life merit further attention in future research. Received September 3, 2015; accepted March 16, 2016